Mastering the art of archery - Adenan, Nur Dalila; Abdullah, Nasiha; Ngah, Nazlin Emieza; Abdul Talib, Nurafida; Mohamad Azmin, Nur Azwani (Fakulti Pengurusan Perniagaan, UiTM Terengganu, 2023)
Archery is a sport that has been known for centuries. Archery has experienced a resurgence in popularity in recent years as more people discover its uniqueness and difficulty. In addition, archery is an excellent choice of sport and is suitable for individuals from all walks of life, whether they wish to compete at the highest level or are simply seeking a new hobby that provides benefits for their physical and mental health. Archery requires both physical and mental skill, making it a great sport for people of all ages and abilities. Archery is a sport of strategy.